Den digitale dobbeltgænger - Lauritsen, Peter (Politik, 2015)
Today, many practices related to security, safety, welfare and even entertainment are based on gathering and using personal data. is article argues that this kind of surveillance, often labeled dataveillance, entails the production of ‘data doubles’, which act as proxies for the individual. Using the concepts of surveillant assem- blages and oligoptica the article interprets data doubles as 1) produced by networks, 2) fragile, and 3) limited in scope. is line of thought implicates empirical interest in the production and purpose of speci c and het- erogeneous data doubles rather than assuming an a priori critical attitude to the nature and function of these.